2013
DOI: 10.3382/ps.2012-02581
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drug-resistant Enterobacteriaceae in retail poultry and beef

Abstract: There has been increasing concern on the emergence of multidrug-resistant foodborne pathogens from foods of animal origin, including poultry. The current study aimed to evaluate antibiotic-resistant Enterobacteriaceae from raw retail chicken/turkey parts (thigh, wings, breast, and ground) and beef meat (ground and chunks) in Middle Tennessee. Resistance of the collected Enterobacteriaceae to a panel of antibiotics was determined by the Kirby-Bauer disk diffusion test. Retail meats were also assayed for the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 57 publications
6
27
0
2
Order By: Relevance
“…They could emerge as foodborne pathogens as they were previously isolated from outbreaks. An earlier study reported the isolation of multidrug-resistant Morganella morganii in US retail poultry and beef [37], and Serratia spp. (14.3%) were among the most prevalent contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…They could emerge as foodborne pathogens as they were previously isolated from outbreaks. An earlier study reported the isolation of multidrug-resistant Morganella morganii in US retail poultry and beef [37], and Serratia spp. (14.3%) were among the most prevalent contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of reports of antimicrobial resistance in bacteria found in meat products [28,29]. However, there are relatively fewer such reports on produce [30].…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of Enterobacteriaceae in chicken carcass came from contents of intestinal tract during evisceration 6 . Enterobacteriaceae is used as hygiene indicator in food industry.…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae is used as hygiene indicator in food industry. The study on contamination of Enterobacteriaceae in meat from retail stores in Tennessee, USA 6 found the contamination level of Enterobacteriaceae in raw meats ranged from 3.26 log10 cfu/g to 4.94 log10 cfu/g. The contamination level of Enterobacteriaceae in duck meat in this study was relatively same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation